The immunological synapse: a molecular machine controlling T cell activation. - Grakoui, A; Bromley, S; Sumen, C; Davis, M; Shaw, A; Allen, P; Dustin, M (1999)
The specialized junction between a T lymphocyte and an antigen-presenting cell, the immunological synapse, consists of a central cluster of T cell receptors surrounded by a ring of adhesion molecules. Immunological synapse formation is now shown to be an active and dynamic mechanism that allows T cells to distinguish potential antigenic ligands. Initially, T cell receptor ligands were engaged in an outermost ring of the nascent synapse. Transport of these complexes into the central cluster was dependent on T cell receptor-ligand interaction kinetics. Finally, formation of a stable central cluster at the heart of the synapse was a determinative event for T cell proliferation.